Emotions, ethics and decision-making - Zerbe, W. J.; Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945- (Research on emotion in organizations ;, 2008)
The rapidly growing recognition of the importance of emotion in understanding all aspects of organizational life is facilitating the development of focused areas of scholarship. The articles in this volume represent a selection of the best papers presented at the sixth International Conference on Emotions and Organizational Life (held in Atlanta, in July 2006), complemented with invited chapters by leading scholars in the field. The theme of this volume, Emotions, Ethics and Decision-making, concerns the role of emotions in decision-making in general, and also more specifically the special place of emotions in decisions that have an ethical character. It begins by looking at the influence of emotions on strategic decisions, among entrepreneurs, in the case of workplace proenvironmental behaviors, as well as how emotional intelligence contributes to problem solving. Emotions are particularly present in ethical decisions, largely because of the close connection between personal identity, for which values are central, and feelings about the self. Specific chapters look at emotions experienced as a result of ethical dilemmas, the role of anger and justice perceptions, the role of attributions and emotional intelligence in ethics perceptions, and at emotions in three specific contexts: emotional labor, whistle-blowing and sexual harassment. Finally the volume comes full circle in an examination of how top executives engage in change that is truly congruent with the ethical values of internal and external constituents.